OP0129 Drug survival on anti-tnf-alpha in psoriatic arthritis patients with axial involvement and analysis of predictors. (12th June 2018) - Lopriore, S.; Cacciapaglia, F.; Perniola, S.; Anelli, M.G.; Lopalco, G.; Scioscia, C.; Coladonato, L.; Laselva, G.; Lapadula, G.; Iannone, F.
Abstract : Background: A few studies have focused on the clinical outcomes in predominant axial Psoriatic Arthritis (PsA) patients treated with anti-TNF-α agents 1–3 in real-life settings. Objectives: Primary endpoint: to evaluate drug survival on anti-TNF-α agents in PsA patients with axial involvement or axial and either polyarticular or oligoarticular peripheral arthritis. Secondary endpoints: to evaluate the presence of any predictor of discontinuation of anti-TNF in PsA patients with axial involvement and to investigate whether peripheral arthritis may impact the discontinuation for ineffectiveness in patients with axial disease. Methods: 415 biologic therapy-naive PsA patients (CASPAR criteria) starting a first TNF-inhibitor from January 2010 to December 2016 were screened. Among these, 87 had axial involvement (ASAS criteria) with imaging arm (X-ray or MRI) and were enrolled: 40 with axial and polyarticular peripheral PsA (Axe +Poly PsA), 38 with axial and oligoarticular peripheral PsA (Axe +Oligo PsA) and 9 with only axial disease (Ax-PsA). At baseline and at last available visit or drug discontinuation, we collected age, gender, disease duration, BMI, HLA-B27, nail psoriasis and/or dactylitis, TJC, SJC, ESR, CRP, enthesitis, LEI, DAPSA, BASDAI, ASDAS-CRP, PASI, HAQ, intake of glucocorticoids and DMARDs, anti-TNF therapy discontinuation and reasons of discontinuation. Drug survival was evaluated by Kaplan-Meier life table method, comparison of survival curves with Log-rank test and baseline predictors of drug discontinuation with Cox regression analysis. Results: At baseline, Axe +Poly PsA patients had significantly higher peripheral (DAPSA) and axial disease activity (BASDAI, ASDAS-CRP). Stratifying patients by subset of disease, the median of treatment was 51 months (95% IQR 24.87–77.13) for Ax-PsA group, 50 months (95% IQR 28.39–71.61) for Axe +Oligo PsA group, 30 months (95% IQR 11.84–48.15) for Axe +Poly PsA group (figure 1). Axe +Oligo PsA patients had significantly higher persistence on TNFi rather than Axe +Poly PsA patients (log rank test, p=0.03). Axe +Poly PsA patients had higher risk of stopping TNFi (Cox regression, HR 3.75) and significantly higher percentage of discontinuation for ineffectiveness rather than for an adverse event (χ2 test, p=0.0009). At last observation, Axe +Poly PsA patients had higher DAPSA but no difference in axial disease activity (t-STUDENT test, Mann-Whitney test). Conclusions: PsA subsets seems to have different features, behaviour, clinical response and drug survival on TNF-inhibitors. Axe +Poly PsA subset seems to be more aggressive and difficult to treat. Anti-TNF-α blockers may perform differently in PsA: a more accurate analysis of the clinical disease subsets may improve our knowledge and better management of PsA in daily practice. References: [1] Lubrano E, et al. Clin Exp Rheumatol2011Jan-Feb;29(1):80–4. [2] Lubrano E, et al. J Rheumatol2016May;43(5):918–23. [3] Perrotta FM, et al. J Rheumatol2016Feb;43(2):350–5. Disclosure of Interest: None declared